Komersialisasi Menara Masjid Sebagai Base Transceiver Station (BTS) Perspektif Fikih Berbasis Maslahah - Abdul Hakim; Imam Syafi'i (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2020)
In the implimentation of these research activities, then an intensive and deep we dig into the data that is primary an secondary literature of several yellow book, considering that this study are typologically prescriptive explanatory, the purpose of this study was to describe the breadth and depth of the object of our research purpose, of this we do after analyzing of data we obtained, in wich the implementation we used the method of content analysis, that is a pttern of oure text assessment of various literature related and associated with the object of this study, to then take the yarn conclusions as answer to same problems we formulated earliner. the views of jurisprudence space to the commercialization of minarets as telecommunications towes is included of a lease contract, which party takmir as mu'jir, the telecommunications company as musta'jir and towers being rented is musta'jar and ton contract lika this an be fine. Because although there are opinions that do not allow either makruh or haram, all of them groundless if it would cause distress of mafsadat, and there is no need. As for now, a lot of management or commercialize takmir mosque to tower in order to prosper, empower and increase operational funds the moeques and to optimize the function of one part of the mosque building. And all these takmir efforts are froms of an effort to create the benefit of the mosque.